(untitled) (lectio difficilior, 2021)
The saturation of Ezekiel 23 with sexual metaphors, violent images, and its negative framing of female sexuality has brought this text to the attention of feminist exegetes. I follow their approach of unveiling the misogynistic concepts and language of this biblical text. Therefore, this article inquires about how male dominance over female bodies and sexuality is performed. I engage Ezekiel 23 as a literary composition with Gayatri S. Spivak’s concept of othering and Homi K. Bhabha’s concept of mimicry. Thereby, I expose the sexualized female body and the gendered, misogynic concepts as well as the sexualized violence as a means of male domination. Thus, I demonstrate how the literary strategies of othering, feminization, and mimicry serve the agency of the book of Ezekiel and produce YHWH as the ultimate virile character in the story of Ohola and Oholiba. Thus, I argue that anti-imperial and misogynic imagery are inextricably linked in Ezekiel 23. Consequently, my final chapter engages the question, how this text can be read “against the grain”.